Fracture Characteristics and Fatigue Damage of Noncoplanar Fractured Rocklike Specimens under Uniaxial Graded Cyclic Loading and Unloading - Gui-cheng He; Wen-yuan Wu; Yun Wang; Yong-ming Xue; Bing Dai; Zhi-jun Zhang (Geofluids)
To study the fracture characteristics and fatigue damage of fractured rock masses, noncoplanar fractured rocklike specimens prepared using cement mortar were used for a graded cyclic loading–unloading test. The results showed that the two ends of the horizontal crack were the main stress concentration areas, and they inhibited crack initiation of the inclined fracture. With increasing crack inclination, the inhibitory effect became more obvious. Under the condition that the lower limit stress is constant, as the upper limit stress increases, energy dissipation of the specimen increases, becoming relatively stable in each stage of the cycle. With increasing crack inclination, the increase in the energy dissipation value decreases. Specimens with large changes in the shape of their hysteresis loop tend to exhibit large fluctuations in the elastic modulus. As the loading progressed, the elastic modulus exhibited a downward trend, and the damping ratio tended to be stable. The change in the damping ratio is affected by the dynamic elastic modulus and area of the hysteresis loop. Based on the Weibull probability distribution function, the evolution curve of the damage variable of the specimen can be obtained. This curve reflects the trend of the damage change of the rocklike specimens under various levels of cyclic loading and unloading.